Dinamika Konflik Agraria dan Ketimpangan Tata Kelola:: Studi Kasus Sengketa Lahan di Desa Batu Mila - Hendra Triawan Sudaryo Putra; Muhammad Ramli AT; Ridwan Syam (Journal of Peace, Security and Democracy, 2025)
The land dispute in Batu Mila Village reflects the complex dynamics of the relationship between the community, government, and private sector in the control and utilization of agrarian resources. This study aims to uncover the root causes, actors involved, and patterns of interaction that shape the escalation and resolution of conflicts, with a focus on local social, economic, and political dimensions. Using a qualitative approach with in-depth interviews, field observations, and document reviews, this research found that the dispute was triggered by overlapping ownership claims between villagers and companies, exacerbated by weak law enforcement, unclear boundaries, and minimal community participation in decision-making processes. The analysis results indicate the existence of power asymmetries that affect community access to land and fuel distrust in formal institutions. This study emphasizes the importance of strengthening community-based conflict resolution mechanisms, consistent law enforcement, and the integration of local wisdom into land management policies. These findings not only contribute to the literature on agrarian conflict sociology but also offer practical recommendations for policymakers and local actors to prevent similar conflicts in the future.